Prognostic nomogram for diffuse large B‐cell lymphoma incorporating the International Prognostic Index with interim‐positron emission tomography findings. Issue 8 (6th August 2013) - Chow, A.; Phillips, M.; Siew, T.; Cull, G.; Augustson, B.; Ward, M.; Joske, D.
Abstract: Background/Aims: Results from interim‐positron emission tomography (PET) studies in diffuse large B‐cell lymphoma (DLBCL) patients are varied. We evaluated the prognostic value of interim‐PET in our centre. To improve concordance, interim‐PET was combined with the International Prognostic Index (IPI). Methods: We retrospectively reviewed 100 new consecutive DLBCL patients treated with immunochemotherapy from 2005 to 2010. Twenty‐four patients did not receive interim‐PET and were excluded. Interim‐PET images were re‐examined using a qualitative assessment technique. Progression‐free survival (PFS) and overall survival (OS) were analysed by the Cox proportional hazards model and prognostic accuracy was assessed using Harrell's C statistics (C). Results: Eleven patients were positive, and 65 were negative at interim‐PET. The 2‐year OS and PFS were 70.8% and 60.0%, respectively, in the PET‐negative group, 36.4% and 36.4% for the PET‐positive group (log‐rank P ‐value 0.0008 for PFS, 0.0001 for OS). The IPI and interim‐PET were minimally correlated. On Cox regression analysis, both were significant indicators of PFS ( P < 0.001 and P = 0.002 respectively). The prognostic accuracy for PFS of a negative PET result was limited (C = 0.63), as it was for IPI (C = 0.75), but with the two indicators combined, the predictive accuracy was improved (C = 0.81). A nomogram, predictive for relapse‐free survival at 2 years, was constructed. Conclusion: In DLBCL patients treated with immunochemotherapy, the IPI and interim‐PET provide independent prognostic information. In combination, a more powerful predictive model may be created as a nomogram. This can be refined in prospective trials and may help clinical decision making.